Ciliopathies and oligogenic phenomena - Katsanis, Nicholas (Henry Stewart Talks, 2015)
Ciliopathies: multisystemic disorders caused by structural and/or functional defects of the primary cilium, Mutations in almost 100 genes discovered to date, no clear pattern between specific genes and specific phenotypes, Functional interpretation of variants critical for understanding the contribution of alleles to disease severity and pleiotropy, A systems-based consideration for the total amount of pathogenic variation in the ciliary proteome begins to predict clinical substructure